2011
DOI: 10.1186/1471-2180-11-118
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell time-lapse analysis of depletion of the universally conserved essential protein YgjD

Abstract: BackgroundThe essential Escherichia coli gene ygjD belongs to a universally conserved group of genes whose function has been the focus of a number of recent studies. Here, we put ygjD under control of an inducible promoter, and used time-lapse microscopy and single cell analysis to investigate the phenotypic consequences of the depletion of YgjD protein from growing cells.ResultsWe show that loss of YgjD leads to a marked decrease in cell size and termination of cell division. The transition towards smaller si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In E. coli, a decrease in cell size was found to be associated with a reduced growth during the stringent response (34,35,41). We noticed that C. crescentus cells accumulating (p)ppGpp often appeared smaller under the microscope (see Fig.…”
Section: Resultsmentioning
confidence: 85%
“…In E. coli, a decrease in cell size was found to be associated with a reduced growth during the stringent response (34,35,41). We noticed that C. crescentus cells accumulating (p)ppGpp often appeared smaller under the microscope (see Fig.…”
Section: Resultsmentioning
confidence: 85%
“…To be able to reconstruct a proper PALM image, it is of utmost importance that cells remain immobile during the whole acquisition time. This has been ordinarily achieved by immobilizing cells in agarose pads, which have the added advantage that they allow for time-lapse imaging under conditions that promote normal growth [13], [14], [27], [28].…”
Section: Resultsmentioning
confidence: 99%
“…Together these observations imply that cells require an intact EKC/KEOPS complex to work properly and if this is not achieved, cells experience growth problems as a result of improper translation. The only ortholog of components of the KEOPS complex in Escherichia coli , Kae1 (YgjD) is essential 24 and using an inducible construct it has been shown that YgjD is also required for cell growth 25 . These results suggest that t 6 A synthesis is the most primitive function of Kae1, incorporated during evolution into the EKC/KEOPS complex to fulfill physiological requirements of eukaryotic and archeal cells.…”
Section: The Ekc/keops Complex Is Required For Trna Modification and mentioning
confidence: 98%